Decriminalisation of sexual activities in same-sex relationships between consenting adults in Botswana - Moruipisi, Dorothy Nametsegang (Department of Private Law, 2016)
The Constitution of Botswana under section 3 read in conjunction with section 15, guarantees all Batswana equal enjoyment of fundamental rights and freedoms irrespective of one's race, colour, sex, tribe, status etc. Section 15 (3) further qualifies what conduct will be deemed discriminatory. Section 9 also ensures that every person's right to privacy is protected except where the person has given consent to have their right violated. Notwithstanding, the same Constitution permits limitations to the full enjoyment of these fundamental rights and freedoms on matters of public interest, public morality or for protecting the interests and rights of others. However, limitations in order to pass the constitutional scrutiny, must take place in terms of the authority of the law and have to be reasonably justifiable in a democratic society. Criminalisation of same sex conduct which is provided for under the Penal Code is a prima facie violation of the above constitutional provisions, which is, as it will be argued here, not capable of justification. The Penal Code violates section 3 of the Constitution, which aims at promoting equality of all citizens. It does so by criminalising certain sexual conducts committed by a certain group of persons (those involved in same-sex relationships), and not extending the same treatment to heterosexuals−thereby creating a discriminatory act. A prima facie violation of the right to privacy under section 9 is also established by this criminalisation. It will be argued that permitting the law to traverse into the sexual life of grown up people and regulate their sexual behavior, is not only a violation of their privacy but also dignity. Prescribing who people should fall in love with and who they should engage in sexual conduct with, violates individual autonomy―freedom of choice, which freedom should be inherent in every individual. Section 15 of the Constitution is also violated in the sense that, although its objective is to eradicate any form of discrimination, permitting discrimination on the basis of sexual orientation through criminalising same sex sexual conduct between consenting adults, defeats the very purpose that the provision is aimed at achieving. This paper acknowledges the existence of the rights to religious beliefs and practices as well as the culture and morals of the majority in Botswana. Notwithstanding, it will be argued that, taking these rights into consideration, it still does not justify the violations that the Penal Code establishes through criminalisation. This paper will recommend that, because courts are vested with the powers to declare any law or policy which it finds unconstitutional, they should thus declare those provisions of the Penal Code null and void to the extent of their unconstitutionality.